(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this research were 1) to study tourists’ behavior and service marketing factors affecting their decision to visit Ayothaya Floating Market in Phra Nakhon Si Ayutthaya Province during the crisis, and 2) to validate the model of tourists’ behavior and service marketing factors affecting their decision to visit Ayothaya Floating Market in Phra Nakhon Si Ayutthaya Province during the crisis. This research was a mixed methods research through quantitative and qualitative methods. For the quantitative research, 17 observable variables were explored and collected from 340 tourists visiting Ayothaya Floating Market. For the qualitative research, data were collected from 9 experts related to the floating market service business, obtained based on a purposive sampling. Research instruments were a questionnaire and semi-structured interview. Data were analyzed with LISREL program, Structural Equation Model (SEM). The results of this research indicated as follows: tourists’ behavior and service marketing factors affecting their decision to visit Ayothaya Floating Market in Phra Nakhon Si Ayutthaya Province during the crisis were consistent and harmonious with the empirical data. The results of calculating index of consistency (IOC) were as follows: χ2 = 199.78, df = 109, χ2 / df = 1.83, CFI = 0.97, GFI = 0.94, SRMR = 0.051, RMSEA = 0.050. 2. Factors affecting tourists’ decision to visit Ayothaya Floating Market included tourist’s behavior and service marketing factors, respectively.